Effects of Chinese Herbal Medicines on the Risk of Overall Mortality, Readmission, and Reoperation in Hip Fracture Patients - Cheng, Chi-Fung; Lin, Ying-Ju; Tsai, Fuu-Jen; Li, Te-Mao; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Liu, Xiang; Li, Ming-Ju; Ban, Bo; Liang, Wen-Miin; Lin, Jeff Chien-Fu (Frontiers in Pharmacology, 2019)
Hip fracture is a major public health concern, with high incidence rates in the elderly worldwide. Hip fractures are associated with increased medical costs, patient dependency on families, and higher rates of morbidity and mortality. Chinese herbal medicine (CHM) is typically characterized as cost-effective and suitable for long-term use with few side effects. To better understand the effects of CHM on hip fracture patients, we utilized a population-based database to investigate the demographic characteristics, cumulative incidence of overall mortality, readmission, reoperation, and patterns of CHM prescription. We found that CHM usage was associated with a lower risk of overall mortality (P-value = 0.0009; adjusted HR: 0.47, 95% CI: 0.30–0.73), readmission (P-value = 0.0345; adjusted HR: 0.67, 95% CI: 0.46–0.97), and reoperation (P-value = 0.0009; adjusted HR: 0.57, 95% CI: 0.40–0.79) after adjustment for age, type of hip fracture, surgical treatment-type, and comorbidities. We also identified the herbal formulas, single herbs, and prescription patterns for the treatment of hip fracture by using association rule mining and network analysis. For hip fracture patients, the most common CHM co-prescription pattern was Du-Zhong (DZ) → Xu-Duan (XD), followed by Du-Huo-Ji-Sheng-Tang (DHJST) → Shu-Jing-Huo-Xue-Tang (SJHXT), and Gu-Sui-Bu (GSB) → Xu-Duan (XD). Furthermore, XD was the core prescription, and DZ, GSB, SJHXT, and DHJST were important prescriptions located in cluster 1 of the prescription patterns. This study provides evidence for clinical CHM use as an adjunctive therapy that offers benefits to hip fracture patients.